Suspension Array for Multiplex Detection of Eight Fungicide-Resistance Related Alleles in Botrytis cinerea - Zhang, Xin; Xie, Fei; Lv, Baobei; Zhao, Pengxiang; Ma, Xuemei (Frontiers in Microbiology, 2016)
A simple and high-throughput assay to detect fungicide resistance is required for large-scale monitoring of the emergence of resistant strains of Botrytis cinerea. Using suspension array technology performed on a Bio-Plex 200 System, we developed a single-tube allele-specific primer extension (ASPE) assay that can simultaneously detect eight alleles in one reaction. These eight alleles include E198 and 198A of the β-Tubulin gene (BenA), H272 and 272Y of the Succinate dehydrogenase iron–sulfur subunit gene (SdhB), I365 and 365S of the putative osmosensor histidine kinase gene (BcOS1), and F412 and 412S of the 3-ketoreductase gene (erg27). This assay was first established and optimized with eight plasmid templates containing the DNA sequence variants BenA-E198, BenA-198A, SdhB-H272, SdhB-272Y, BcOS1-I365, BcOS1-365S, erg27-F412, and erg27-412S. Results indicated that none of the probes showed cross-reactivity with one another. The minimum limit of detection for these genotypes was one copy per test. Four mutant plasmids were mixed with 10 ng/μL wild-type genomic DNA in different ratios. Detection sensitivity of mutant loci was 0.45% for BenA-E198A, BcOS1-I365S, and erg27-F412S, and was 4.5% for SdhB-H272Y. A minimum quantity of 0.1 ng of genomic DNA was necessary to obtain reliable results. This is the first reported assay that can simultaneously detect mutations in BenA, SdhB, BcOS1, and erg27.